FRAMING OF NEWS ON VIOLENCE AGAINST WOMEN IN THE HOUSEHOLD ANALYSIS OF THE CRIMINAL NEWS SHOW PROGRAM “PATROLI” ON INDOSIAR TELEVISION STATION - Windu Tiastuti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Cases of domestic violence with female victims in Indonesia are very high. The evidence of cases reported to the authorities, as well as to the system created by related institutions, is very high and continues to increase from year to year. The high incidence of violence against women in the household cannot be separated from the patriarchal culture that our society still adheres to. The number of incidents is believed to be like an iceberg because not all incidents are reported to the authorities and resolved legally. The fact of the occurrence of cases of violence against women in the household is not only in the form of reported data, but can also be known to the wider community through news coverage in the mass media, one of which is in the crime news show program “Patroli” on the Indosiar National Television Station. Mass media such as television, which contains a combination of audio and visual information, has the potential to influence the way people think and their opinions, through the framing of the news coverage of cases that are aired.